Home-Based Exercise Programs for the Oldest-Old to Attenuate Physical Frailty: A Scoping Review - da Silva Capanema B.* (2024)
© Serdi 2024.Background: With the significant increase in the number of long-lived elderly people living at home, the development of effective physical exercise interventions at home becomes essential to preserve their independence and delay institutionalization and hospitalizations. Objective: to map and describe home exercise programs for elderly people aged 80 or over with physical frailty. Methods: The scoping review allowed the inclusion of several methodologies and varied perspectives, maintaining rigor in accordance with the methodological steps of the Joanna Briggs Institute (JBI). The systematic search covered studies available until May 2023 in five databases and gray literature. Frailty was assessed according to the criteria of Fried et al. (2001), physical performance scale (SPPB), such as gait and mobility, and the authors’ assessment of reduced physical function were considered. The study followed the PRISMA Extension for Scoping Reviews (PRISMA-ScR) guidelines and is publicly available in the Open Science Framework (OSF) repository. Results: Twenty studies were identified that met the inclusion criteria. The total number of elderly people investigated in the study was 1,796. The most important physical interventions were muscular strength training, mainly of the lower limbs, together with flexibility, balance, aerobic and functional training. These home interventions have demonstrated potential, safety and effectiveness in preventing and alleviating physical frailty. These home interventions demonstrated potential, safety and effectiveness in preventing and alleviating physical frailty, adherence in most studies varied between 72% and 89%. Conclusion: This study will allow us to design home-based exercise interventions, potentially providing practical solutions and assisting healthcare professionals in home-based interventions to reduce and mitigate physical frailty in the growing population of older adults. It will also help fill the existing knowledge gap and provide recommendations for future research.